Assessment of Images of Birds Captured by Low-Cost Drone using Agisoft Photoscan - Aqil Nizamudin, Adry; Mazlina Wan Mohamed, Wan (International Journal of Engineering and Technology, 2018)
Birds are significant flying vertebrates in agriculture, thus the search for effective bird detection technique has been getting increasingly necessary. This paper proposes a low-cost technique to detect birds using off-the-shelf drone with built-in camera. The objective of this research is to identify the number of birds at the selected area based on images captured by drone at different altitude. The images were analysed using Agisoft Photoscan software. The research was carried out at Tasik Shah Alam, and focused on storks. The results indicated that the most number of storks detected were at 15 and 20 metres. This signifies that the closer the camera is to the birds, the clearer the images will be. At lower altitude, the images captured are found to be more precise than at higher altitude. This is probably due to the vegetation blocking the view of the camera at higher altitude. It is recommended to use thermal camera compared to visual camera due to the former capability of detecting hidden birds based on heat generated, where visual camera could not capture.Â